The Technological Context and Organizational Context Cross-Border ECommerce Small and Medium-Sized Enterprises' Performance in Hebei - Zhang Jingjing; Sidah Idris (Faculty of Business, Economics and Accountancy Universiti Malaysia Sabah, 2023)
The scale of cross-border e-commerce (CBEC) transactions in China has been developing rapidly. In 2011, the total scale of cross-border e-commerce transactions in China was 1.8 trillion yuan, growing to 12.5 trillion yuan in 2020, with the average annual year-on-year growth rate close to maintaining a high level. However, overall, the growth rate is decreasing. The support from the government and national policies has promoted the rapid development of cross-border e-commerce in China. The aim of this study is to investigate the demand for information technology in international trade as it has spawned the development of crossborder e-commerce. The study will focus on the technological, and organizational contexts and their effects on SMEs' performance in Hebei Province. It is the embodiment of a new economic form, paving the way for a new path of development by combining the Internet with traditional industries. This study will explore the influencing factors of cross-border e-commerce SMEs' performance in Hebei Province. The study adopts a systematic literature analysis on crossborder e-commerce SMEs in China, which is still limited. This study plays a significant role inindustry innovations that have been emerging by focusing on new industries, new models, and new engines for foreign trade.